2010
DOI: 10.3382/ps.2009-00130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymol and carvacrol feed supplementation on lipid oxidation in broiler meat

Abstract: Poultry meat is particularly prone to oxidative deterioration due to its high concentration of polyunsaturated fatty acids. The present study evaluates the effects of thymol and its isomer carvacrol on lipid oxidation when supplemented to the feed. Supplementation with the antioxidant butylated hydroxytoluene was used as a positive control. Thus, broiler chickens were assigned to 1 of 4 treatments: vehicle (control), 150 mg/kg of butylated hydroxytoluene (positive control), 150 mg/kg of thymol, or 150 mg/kg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(117 citation statements)
references
References 31 publications
9
97
1
10
Order By: Relevance
“…It was confirmed in our experiment, in evaluation of breast and thigh muscles of Hubbard JV chickens with application of propolis extract in their nutrition. Results of our experiment did not confirm the results of Šperňáková et al (2007) and Luna et al (2010), who applied extract of thymol and carvacrol (powdered rosemary) and found the higher stability of thigh muscle compared with breast muscle. In our experiment, we found opposite effect.…”
Section: Time Of Storagecontrasting
confidence: 99%
“…It was confirmed in our experiment, in evaluation of breast and thigh muscles of Hubbard JV chickens with application of propolis extract in their nutrition. Results of our experiment did not confirm the results of Šperňáková et al (2007) and Luna et al (2010), who applied extract of thymol and carvacrol (powdered rosemary) and found the higher stability of thigh muscle compared with breast muscle. In our experiment, we found opposite effect.…”
Section: Time Of Storagecontrasting
confidence: 99%
“…The results of the present study showed that the breast meat of broilers fed 400 ppm of barbatimão was capable of retaining water inside the muscle fibers and, therefore, being more tender than the meat of those fed the control diet. These results are in agreement with other studies evaluating plant extract supplementation in broiler diets (Lahucky et al, 2010;Luna et al, 2010).…”
Section: Meat Tendernesssupporting
confidence: 93%
“…Promising results have been obtained by research in this field so far, when supplementation of some herbal substances had a positive impact not only on the growth performance of broiler chickens, but also on their antioxidant status as well as on the oxidative stability of meat. For these reasons, use of natural "herbal" antioxidants in the fattening of broilers is considered to be a suitable method to achieve better antioxidant status of poultry, and also higher oxidation stability of poultry meat during storage (Luna et al 2010;Jayasena and Jo 2014). Agrimony (Agrimonia eupatoria L.) and sage (Salvia officinalis L.) are among the most frequently studied herbs due to their high content of active substances with antioxidant properties (Giao et al 2009;Ryzner et al 2013).…”
Section: Antioxidant Status Lipid Oxidation Herbal Extracts Poultrymentioning
confidence: 99%